Log In Start studying!

Select your language

Suggested languages for you:
Answers without the blur. Sign up and see all textbooks for free! Illustration


Found in: Page 133


Book edition Common Core Edition
Author(s) Ron Larson, Laurie Boswell, Timothy D. Kanold, Lee Stiff
Pages 183 pages
ISBN 9780547587776

Answers without the blur.

Just sign up for free and you're in.


Short Answer

Solve the equation. Check your solution.


The solution for the equation 2-4h-13=37+13h is h=-3.

See the step by step solution

Step by Step Solution

Step 1 – Separate the variable and constants

Write the original equation and separate the variable and constants.

24h13=37+13h8h26=37+13h8h13h26=37+13h13h Subtract 13h from both sides21h26=3721h2637=3737 Subtract 37 from both sides21h63=021h=63

Step 2 – Solve for h

Now, divide both sides of the equation by -21.


Therefore, the solution of the equation is h=-3.

Step 3 – Check the solution 

To check the solution, write the original equation and substitute the value of h.


Now, substitute h=-3 and check the result.


As the left-hand side is equal to right hand side, this signifies that the solution is correct.

Recommended explanations on Math Textbooks

94% of StudySmarter users get better grades.

Sign up for free
94% of StudySmarter users get better grades.